Anesthesia, pain management and surgical approach of ovariectomy or orchiectomy in six Egyptian fruit bats (Rousettus aegyptiacus): A case report - Tal, Smadar; Shilo-Benjamini, Yael (Frontiers in Veterinary Science, 2023)
The purpose of this report is to describe the anesthetic and analgesic management and the surgical procedures of gonadectomy in six (four females and two males) healthy adult Egyptian fruit bats (Rousettus aegyptiacus). Bats were anesthetized with a combination of alfaxalone, midazolam, and morphine administered subcutaneously. Incisional line infiltration using bupivacaine was administered in all bats, and additional bilateral intratesticular injection was administered in the males. Ovariectomy was performed via a dorsal approach, by bilateral midline skin incisions at the paralumbar fossa level. Orchiectomy was performed via a ventral approach, by bilateral midline incisions of scrotal skin above the testes. Following surgery, all bats were administered flumazenil for midazolam reversal, and meloxicam for postoperative analgesia, subcutaneously. All bats recovered from anesthesia uneventfully. Bats were monitored for complications up to 10 days following surgery, when skin sutures were removed. No morbidities or mortalities occurred during this period in any of the bats. In conclusion, ventral approach orchiectomy and dorsal approach ovariectomy using the injectable combination alfaxalone-midazolam-morphine in conjunction with local anesthesia and meloxicam are feasible procedures in Egyptian fruit bats and can be performed with relative ease. However, further studies using these techniques in a larger group of bats should be performed to establish their safety.